2002
DOI: 10.1076/ceyr.24.3.196.8302
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 2 (HIV-2) vector-mediated in vivo gene transfer into adult rabbit retina

Abstract: HIV-2 viral vector may be a useful gene delivery vehicle for retinal photoreceptor cells and ganglion cells. It deserves further exploration to investigate its potential merit in long term gene therapy protocols and in other animal species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Some studies have observed limited transduction of the inner retina when HIV-1 vectors are delivered intravitreally, 8 whereas others have reported some transduction of RGCs following intravitreal injection of HIV-2 vectors. 30 DNA-and RNA-based technologies to modify RGC gene expression Nonviral gene transfer strategies have the advantage of circumventing the safety concerns that stem from the potential immunogenic response and risk of chromosomal integration associated with viral vectors. The downside of nonviral approaches is that they yield low transduction rates, resulting in limited and often short-lived gene expression in vivo.…”
Section: Tools For Gene Delivery To Injured Rgcsmentioning
confidence: 99%
“…Some studies have observed limited transduction of the inner retina when HIV-1 vectors are delivered intravitreally, 8 whereas others have reported some transduction of RGCs following intravitreal injection of HIV-2 vectors. 30 DNA-and RNA-based technologies to modify RGC gene expression Nonviral gene transfer strategies have the advantage of circumventing the safety concerns that stem from the potential immunogenic response and risk of chromosomal integration associated with viral vectors. The downside of nonviral approaches is that they yield low transduction rates, resulting in limited and often short-lived gene expression in vivo.…”
Section: Tools For Gene Delivery To Injured Rgcsmentioning
confidence: 99%
“…Additional transduction of neuroretinal neuronal and glial cells, albeit of variable efficiencies and distributions, is reported using HIV-1, (refs 16-18) HIV-2, (ref. 25) EIAV, (refs 30,33,35) BIV 35 and FIV 36,39,40,42 vectors in rodents, rabbits or NHPs, and by some groups delivering HIV-1 vectors in young rodents 7,10 (Figure 2). Lentiviral Typical transduction profiles of VSV-G-pseudotyped lentiviral vectors harbouring ubiquitous promoters after intraocular delivery in C57Bl/6J mice.…”
Section: Sub-retinal Deliverymentioning
confidence: 99%
“…5,6 OCULAR TRANSDUCTION PROFILES OF LENTIVIRAL VECTORS The transduction properties of HIV-1, (refs 7-24) HIV-2, (ref. 25) SIV, [26][27][28][29] EIAV, 21,[30][31][32][33][34][35] FIV, 24,[36][37][38][39][40][41][42][43] and BIV 44 vectors incorporating a diverse array of envelope pseudotypes and transgene promoters have been evaluated after in vivo and ex vivo delivery in a variety of animal species (Supplementary Tables 1 and 2). Most ocular studies have used vesicular stomatitis virus-G (VSV-G)-pseudotyped vectors incorporating ubiquitous promoters and these are described below unless otherwise stated.…”
Section: Introductionmentioning
confidence: 99%
“…Photoreceptor cell transduction or transfection by early adenovirus, 11 HIV-based lentiviruses 12,13 or various non-viral methods 3 is relatively inefficient, and the duration of transgene expression limited either by silencing of the transgene promoter 14 or through clearance of transduced cells after immune responses to vector proteins. 15 Further development of these vector systems, for example, by the removal of immunogenic viral genes from the vector genome of adenovirus 16 or the removal of bacterial plasmid sequences in DNA mini-circles in non-viral gene transfer 17 has resulted in significant improvements in longevity of expression.…”
Section: Gene Transfer To Photoreceptor Cellsmentioning
confidence: 99%